2021
DOI: 10.3390/microorganisms9061253
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking DNA Extraction Methods for Phylogenomic Analysis of Sub-Antarctic Rhodococcus and Williamsia Species

Abstract: Bacteria containing mycolic acids in their cell envelope are often recalcitrant to cell lysis, so extracting DNA of sufficient quality for third-generation sequencing and high-fidelity genome assembly requires optimization, even when using commercial kits with protocols for hard-to-lyse bacteria. We benchmarked three spin-column-based kits against a classical DNA extraction method employing lysozyme, proteinase K and SDS for six lysozyme-resistant, sub-Antarctic strains of Corynebaceriales. Prior cultivation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
7
0
2
Order By: Relevance
“…Thus, they are similar microorganisms and belong the same order Actinomycetales of Gram-positive bacteria. However, R. erythropolis contains mycolic acids in its cell wall [ 70 , 71 ]. Mycolic acids are long-chain branched fatty acids [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they are similar microorganisms and belong the same order Actinomycetales of Gram-positive bacteria. However, R. erythropolis contains mycolic acids in its cell wall [ 70 , 71 ]. Mycolic acids are long-chain branched fatty acids [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although out of the scope, it is important to highlight the importance of these steps (Pollock et al, 2018 ). In particular, care should be taken to avoid contamination and biases due to DNA extraction and degradation during processing and storage (Han et al, 2019 ; Nahar et al, 2021 ; Sar et al, 2018 ). Comparative studies indicated that the choice of DNA extraction method affects the outcome, with mechanical and/or enzymatic pretreatments being often superior (Gryp et al, 2020 ; Henderson et al, 2013 ).…”
Section: Dna Sequencingmentioning
confidence: 99%
“…Sodium dodecyl sulfate (SDS) is widely applied in many commercial cleaning products, such as soaps, toothpaste, etc . It is also used for DNA and protein extraction in polyacrylamide gel electrophoresis. Due to its common use, SDS has been extensively studied experimentally over the past century via different experimental methods. , From the perspective of colloidal chemistry, the preassemble behavior of SDS is clearly known: the formation of tail-to-tail aligned structures through hydrophobic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium dodecyl sulfate (SDS) is widely applied in many commercial cleaning products, such as soaps, toothpaste, etc. 17 It is also used for DNA and protein extraction 21 in polyacrylamide gel electrophoresis. Due to its common use, SDS has been extensively studied experimentally over the past century via different experimental methods.…”
Section: Introductionmentioning
confidence: 99%